Management of indwelling tunneled pleural catheters: a modified delphi consensus statement - Gilbert, Christopher R.; Wahidi, Momen M.; Light, Richard W.; Rivera, M. Patricia; Sterman, Daniel H.; Thomas, Rajesh; Shojaee, Samira; Shoham, Shmuel; Psallidas, Ioannis; Ost, David E.; Molena, Daniela; Maskell, Nick; et al. (Chest, 2020)
Background - The management of recurrent pleural effusions remains a challenging issue for clinicians. Advances in management have led to increased use of indwelling tunneled pleural catheters (IPC) because of their effectiveness and ease of outpatient placement. However, with the increase in IPC placement there have also been increasing reports of complications, including infections. Currently there is minimal guidance in IPC-related management issues after placement. - Research Question - Our objective was to formulate clinical consensus statements related to perioperative and long-term IPC catheter management based on a modified Delphi process from experts in pleural disease management. - Study Design and Methods - Expert panel members used a modified Delphi process to reach consensus on common perioperative and long-term management options related to IPC use. Members were identified from multiple countries, specialties, and practice settings. A series of meetings and anonymous online surveys were completed. Responses were used to formulate consensus statements among panel experts, using a modified Delphi process. Consensus was defined a priori as greater than 80% agreement among panel constituents. - Results - A total of 25 physicians participated in this project. The following topics were addressed during the process: definition of an IPC infection, management of IPC-related infectious complications, interventions to prevent IPC infections, IPC-related obstruction/malfunction management, assessment of IPC removal, and instructions regarding IPC management by patients and caregivers. Strong consensus was obtained on 36 statements. No consensus was obtained on 29 statements. - Interpretation - The management of recurrent pleural disease with IPC remains complex and challenging. This statement offers statements for care in numerous areas related to IPC management based on expert consensus and identifies areas that lack consensus. Further studies related to long-term management of IPC are warranted.
Gesehen am 10.03.2021